Applications of the Soil, Plant and Rumen Microbiomes in Pastoral Agriculture - Attwood, Graeme T.; Wakelin, Steve A.; Leahy, Sinead C.; Rowe, Suzanne; Clarke, Shannon; Chapman, David F.; Muirhead, Richard; Jacobs, Jeanne M. E. (Frontiers in Nutrition, 2019)
The production of dairy, meat, and fibre by ruminant animals relies on the biological processes occurring in soils, forage plants, and the animals’ rumens. Each of these components has an associated microbiome, and these have traditionally been viewed as distinct ecosystems. However, these microbiomes operate under similar ecological principles and are connected via water, energy flows, and the carbon and nitrogen nutrient cycles. Here, we summarise the microbiome research that has been done in each of these three environments (soils, forage plants, animals’ rumen) and investigate what additional benefits may be possible through understanding the interactions between the various microbiomes. The challenge for future research is to enhance microbiome function by appropriate matching of plant and animal genotypes with the environment to improve the output and environmental sustainability of pastoral agriculture.